The impact of amenities in rural bed and breakfasts on tourists' emotional experience and behavioral intentions: Perspectives from amenity theory - Hui Liu; Jian Zhang; Ziyao Jia; Haiyan Yan (Acta Psychologica)
Amenity theory holds that elements providing pleasant experiences can fulfill emotional needs, attract people, and foster regional development. Utilizing this theory and taking the rural Bed and Breakfasts (B&Bs) in the Yuntai Mountain area as an example, this study constructed a scale for rural B&B amenities through qualitative analysis of tourist reviews. Structural equation modeling was then employed to analyze the impact of these amenities on tourists' emotional experiences and behavioral intentions. The results indicated that rural B&B amenities have five dimensions: environment, facilities, services, functionality, and transportation. All five dimensions positively influenced tourists' emotional experiences, with functionality having the most significant effect. Except for transportation amenities, the other dimensions positively impacted tourists' behavioral intentions. Tourists' emotional experiences positively influenced their behavioral intentions, serving as a key mediating factor that linked rural B&B amenities to behavioral intentions. The findings provide theoretical support and policy implications for the quality enhancement of rural B&Bs, suggesting comprehensive improvements in functionality and service quality to optimize tourists' emotional experiences and promote sustainable development.